An effective e-learning system through learners' scaffolding. (2018) - Bhattacharya, Suman; Chowdhury, Sankhayan; Roy, Samir
Scaffolding is an age-old technique of teacher's intervention to augment and quicken the learners' learning process. While a human teacher has the scope to interact with the learner in contact mode and apply his intelligence to assess the need of such effort, an e-learning system does not have this capacity. This paper presents a scaffolding system for an e-learner. It is targeted towards school level children. The system is structured around the concept of finite state machine to model the cognitive state of the learner. Learning experiences are also taken into consideration. The system is tested on a large number of school going children. Experimental results indicate that under this system, the students achieve their learning objectives to a greater extent with better experience.